Managementt o f non traumatic A vascular Necrosis off Femoral Head at precollapse stage with Core Decompression and tibial Bone Grafting - Kraidi, Baqer Kadhim; Keetan, Alwan Hussein (AL-Kindy College Medical Journal, 2014)
Avascular necrosis have always presented great challenges to orthopedic surgeons and patients, remain in many ways today the unsolved dilemma. Varieties of non-vascularized bone grafting techniques preceded by core decompression have been proposed with varying degrees of success. O bb j ee cc t i vv ee ss : The aim of this study is to review the the value of core decompression and non-vascularized tibial bone strip graft treatment for early stages of non-traumatic osteonecrosis stage II & III according to stein burg staging . M ee t hh oo dd ss : prospectively reviewed 26 patients (32 hips) with osteonecrosis of the femoral head between June 2006 and December 2013 at Imam Ali hospital in Sader city & Al-Wasity teaching hospital. Inclusion criteria were all patients ages 19 years to 50 years and in Stein burg stages II and III . Mean follow-up for 3 year. Exclusion criteria were stage I, IV, V and VI .We used Phemister technique to make a window at the posterior aspect of greater trochanter to remove necrotic bone and packed the excavated area with cortico-cancelloustibial bone strip graft. This study was taking into account ethical evaluation and approval by scientific committee of Arab board. R ee ss uu l t ss: The reported results of treatment for femoral head avascular necrosis was (87.6%) success rate of hips in our cohort of patients with core decompression &non-vascularized tibial bone strip C oo nn cc l uu ss i oo nn ss : None vascularized tibial bone graft effectively reduce donor site morbidity and may defer jointarthroplasty in selected patient stein burg staging